Peningkatan Hard Skill Sistem Informasi Digital Perikanan Tangkap di Era Digital 4.0 - Amir Machmud Suruwaky; Mustasim Mustasim; Misbah Sururi; Vicky Rizky Affandy Katili; Hendra Poltak (Politeknik Kelautan dan Perikanan Sorong, 2021)
fishermen must be adaptive to technological advancement. Community service in the form of increasing the hard skill of the digital information system for fishing fishing in the digital era aims to make it easier for fishermen to carry out their livelihood activities. Activities are carried out online for theory and offline for practice. The target partners were trained as many as 30 people from the hand line fishery community of the Maladum Mes district. The results of monitoring the target partners can practice the material presented.